PERSEPSI GENERASI Z JABODETABEK DALAM PENCARIAN JODOH SECARA DARING (Studi Fenomenologi: Penggunaan Dating Apps Bumble Untuk Mencari Pasangan) - Rahmah Andisa Qurrota'ain (2023)
Finding a partner in online by using the Bumble dating app has become a phenomenon that occurrs after the COVID-19 pandemic hit. Especially generation Z who live in urban areas, they became the largest group of Bumble users and do a lot of activities using the internet. There has been a change in the way of looking for partners in the present and in the past, where in the past people looked for partners directly, not through online media. This study aims to find out the perception of Jabodetabek generation Z in using the Bumble dating app to find a partner, using Symbolic Interaction Theory. The method used is a qualitative research method with a phenomenological approach. Data collection techniques that researchers use are in-depth interviews and observation. In addition, researchers also used the Moustakas phenomenological data analysis technique. The final result of this study is that the perception of Jabodetabek generation Z in using the Bumble dating app to find a partner is a reasonable thing to do at this time and a way to get a partner more easily. Many people use this Bumble dating app based on recommendations from people around them and they also recommend it to their closest environment. Keywords: Dating app, Bumble, Generation Z, Perception